Housing challenges and opportunities among young people in the greater Kuala Lumpur, Malaysia / Mahazril ‘Aini Yaacob - Mahazril ‘Aini , Yaacob (2018)
There have been a number of various housing initiatives promoted by the government, but they are merely inclusive of the lower-income group with the lack of appropriate housing options for the young people. Thus, this thesis explores the challenges faced by young people in their pursuit of adequate housing and to examine the contributing factors to the deficiency of housing policy and practices in Malaysia. The study is conducted using a mixed methods research approach involving a questionnaire survey and support from a series of in-depth interview. The findings reveal that in their pursuit of adequate housing, young people have faced challenges relating to structural, economic and social factors. Through the findings, the study also discovers that young people who are currently renting their accommodation face challenges concerning insecurity of tenure, high rental payment and the poor quality of housing. Concerning the current housing policy and practices, findings have shown that the current housing policy and practices in Malaysia in some manner have responded to the housing problems faced by the young people, but, still deficient in providing housing opportunities due to various factors. Regarding the housing opportunities, young Malaysians believe that they have the chances if factors that shape the opportunities such as affordability, housing knowledge, location and government housing policy are highly deliberated. As such, several restorative strategies are proposed to the policy makers to assist in developing comprehensive housing policy and programmes, encouraging alternative forms of housing assistance, supporting housing development outside the cities, promoting awareness and educating the youth through social marketing strategies, strengthening the cooperation between the Federal, States and other housing agencies and establishing the monitoring and coordinating agency for the better future housing policy and planning. It is hoped that the findings of this research able to contribute towards the inclusive housing practice so that it can respond to the housing needs of young people who desire to live independently.